# 2 - ECE 483 Homework#2 Solution Problem 1 Problem 2-19(a(c...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2/10/10 ECE 483 Homework #2 Solution Problem 1. Problem 2-19 (a)-(c). Note that the results should be in terms of the known constants b 2 , g 1 , g 2 , g 3 , g 4 (forget about the A , A * , p and p * in the problem formulation). Solution: (a) The difference equations are f 1 ( k ) = g 1 f 1 ( k- 1)- g 2 f 2 ( k- 1) + g 3 e ( k ) f 2 ( k ) = g 1 f 2 ( k- 1) + g 2 f 1 ( k- 1) + g 4 e ( k ) y ( k ) = b 2 e ( k ) + f 2 ( k- 1) . (b) Taking the z-transform of the above equations, we have F 1 ( z ) = g 1 z- 1 F 1 ( z )- g 2 z- 1 F 2 ( k ) + g 3 E ( z ) (1) F 2 ( z ) = g 1 z- 1 F 2 ( z ) + g 2 z- 1 F 1 ( z ) + g 4 E ( z ) (2) Y ( z ) = b 2 E ( z ) + z- 1 F 2 ( z ) . (3) From (1), we can solve for F 1 ( z ) as F 1 ( z ) =- g 2 z- 1 F 2 ( k ) + g 3 E ( z ) 1- g 1 z- 1 . Plugging this into (2), we get F 2 ( z ) = g 4 z 2- g 1 g 4 z + g 2 g 3 z ( z- g 1 ) 2 + g 2 2 E ( z ) , which, together with (3), yields the transfer function Y ( z ) E ( z ) = b 2 + z- 1 g 4 z 2- g 1 g 4 z + g 2 g 3 z ( z- g 1 ) 2 + g 2 2 = b 2 + g 4 z- g 1 g 4 + g 2 g 3 ( z- g 1 ) 2 + g 2 2 . (4) (c) After plotting the equivalent signal flow graph (omitted), we find that there are three loops, with gains L 1 = g 1 z- 1 , L 2 = g 1 z- 1 , and L 3 = z- 1 · g 2 · z- 1 · (- g 2 ) =- g 2 2 z- 2 , with the first two being nontouching. Thus, the graph determinant iswith the first two being nontouching....
View Full Document

{[ snackBarMessage ]}

### Page1 / 3

2 - ECE 483 Homework#2 Solution Problem 1 Problem 2-19(a(c...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online